Solar‐Powered Hierarchical Microenvironments with Authigenic Multi‐Field Synergies for Simultaneous Extraction of Freshwater and Cesium - Liuyan Zhu; Lin Zhu; Ting Shi; Ke Zhao; Wenwen He; Lu Han; Zeying Jin; Jialin Kang; Shanfu Sun; Ningning Cao; Zhen Yu (Advanced Science, 2025)
Abstract The escalating global resource and environmental crisis has intensified the urgent demand for efficiently extracting freshwater and critical metals from contaminated water sources, particularly nuclear‐contaminated seawater. Herein, a biomass‐based solar‐powered hierarchical self‐extraction micro‐network (BSSM) is proposed and presented, an innovative system that seamlessly integrates solar‐driven freshwater generation with highly selective cesium ion (Cs+) extraction. A bamboo‐derived biochar with surface‐loaded cobalt oxide nanoparticles (CoO NPs) is prepared and utilized to comprehensively validate the BSSM's efficacy. Leveraging hierarchically engineered microenvironments with authigenic multi‐field synergies, the designed BSSM achieves a high freshwater production rate of 3.3 kg m−2 day−1 and an impressive Cs+ extraction capacity of 34.58 mg g−1. In conclusion, this study establishes a transformative paradigm for resource recovery, providing a scalable and eco‐friendly panacea to address pressing global issues, including water scarcity, nuclear pollution, and resource security.